Perkembangan Teroris Ditinjau dari Konsep Ego Muhammad Iqbal (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
This research aims to describe development of terrorists according to Muhammad Iqbal in his ego concept. This type of research is library research. His method involves exposing the reality of what will happen to individuals who choose to become terrorists. Analyze data using a documented approach in which data is written and written, and data relevant to the research topic is selected and summarized to facilitate understanding. The data analysis technique used descriptive quality. Meanwhile, Muhammad Iqbal's ego theory sees that the phenomenon of the development of terrorism currently occurring among religious communities contains some of Mauhammad Iqbal's thoughts which are in accordance with the real situation of some Indonesian people. Keywords: Human Development, Ego, Terorism